Subharmonically drain pumped wideband lumped and distributed microwave MESFET mixers - Darsinooieh, A H.; Palamutcuoglu, O. (IEEE, 1996)
The nonlinear analysis of subharmonically drain pumped lumped and distributed MESFET mixers have been performed to find the optimum operation conditions. The isolation between the pump and RF ports is readily achieved in drain pumping. Furthermore, since the LO frequency is approximately half of RF signal very simple filter construction is sufficient to provide isolation between the two ports. The efficiency of the mixer is doubled by pumping the drain of two MESFET's with 180° phase difference. In the practical side of this work broadband operation has been achieved from a microwave mixer operating in X band by using microstrip ladder matching structure at RF side and 1:1 suspended microstrip balun for LO injection. The measured conversion gain at optimum bias and LO level conditions is around 1 dB. In the second step of this work the performance characteristics of three sections of unbalance and two sections of balance distributed mixer which are subharmonically drain pumped are considered to achieve wider bandwidth. Different bias conditions and scattering parameters over a frequency range of 2-18 GHz are used for the transistor's parameter optimizing. The whole circuit is also optimized with the aid of nonlinear simulator in Microwave Harmonica Program, version 5.5.